High-performance electrothermal coatings based on natural flake graphite for multifunctional electrothermal applications - Zhi Lei; Shengzhi Duan; Xiaowen Wu; Chaochao Gao; Lianyi Wang; Xin Min; Zhaohui Huang; Minghao Fang; Ruiying Luo; Bingcheng Luo (Journal of Materials Research and Technology, 2023)
Electrothermal elements are used in electronic devices, physiotherapy, and health care due to their lightweight and fast temperature response. However, the high cost and susceptibility to oxidation of traditional electrothermal materials limit their application. In this work, a low-cost, environment-friendly, controllable, and high-performance natural flake graphite-based electrothermal coating is proposed that can be used in various electrothermal applications. The results demonstrate that the morphology and electrothermal properties of the coatings can be controlled based on pressure engineering and the use of various adhesives. The uncompressed electrothermal coatings can reach a maximum temperature of 157.9 °C and a maximum electric conductivity of 27.89 S/m at 36 V, whereas the compressed coatings can reach a maximum temperature of 199 °C at only 18 V and a maximum conductivity of 433.6 S/m, which is 22 times higher than the corresponding uncompressed coatings. This work provides a low-cost, high-performance, and well-attainable industrialization path for the application of natural graphite-based electrothermal coatings in indoor heating, light electrothermal clothing, and snow and ice removal.